CONSUMER ACCEPTANCE TOWARDS SWEET BREAD SUBTITUTED TO MODIFIED TALIPUK FLOUR (MOTAF) AND TEMULAWAK STARCH - Dwi Sandri; Ema Lestari (BPFP Faperta UNIB, 2020)
This study aimed to analyze the consumer's acceptance towards sweet bread substituted to Modified Talipuk Flour (MOTAF) and temulawak starch. This research was conducted using a completely randomized design method (CRD) which consisted of 5 treatments consisting of the ratio of wheat flour, motaf, and ginger starch flour. The sweet bread of these 5 treatments was tested for specific volume and level of consumer preference which consisted of taste, aroma, and texture. The data obtained were then analyzed by ANOVA and followed by further DMRT test at the 5% level. The results showed that consumers could receive sweet bread substituted for Motaf and temulawak starch which in terms of aroma and texture showed no significant difference to bread 100% wheat flour, while in terms of taste in treatment C (substitution of Motaf and Temulawak Starch Flour) has a taste similar to 100% wheat bread with a score of 6.31. Whereas for the specific volume there was a significant difference in each treatment where the bread in treatment C had a greater value than the 100% wheat bread. The addition of temulawak starch will have an effect on the bread yield, the more temulawak starch was added, the quality of the bread will decrease.